Differential GIP/GLP‐1 intestinal cell distribution in diabetics' yields distinctive rearrangements depending on Roux‐en‐Y biliopancreatic limb length. Issue 9 (15th May 2018) - Palha, António M.; Pereira, Sofia S.; Costa, Madalena M.; Morais, Tiago; Maia, André F.; Guimarães, Marta; Nora, Mário; Monteiro, Mariana P.
Abstract: As incretins are known to play an important role in type 2 diabetics (T2D) improvement observed after Roux‐en‐Y gastric bypass (RYGB), our aim was to assess whether increasing the length of RYGB biliopancreatic limb in T2D would modify the incretin staining cell density found after the gastric outlet. Small intestine biopsies ( n = 38) were harvested during RYGB at two different distances from the duodenal angle; either 60‐90 cm ( n = 28), from non‐diabetic ( n = 18) patients, and T2D ( n = 10), or 200 cm ( n = 10) from T2D. GIP and GLP‐1 staining cells were identified by immunohistochemistry and GLP‐1/GIP co‐staining cells by immunofluorescence. Incretin staining cell density at the proximal small intestine of T2D and non‐diabetic individuals was similar. At 200 cm, T2D patients depicted a significantly lower GIP staining cell density (0.181 ± 0.016 vs 0.266 ± 0.033, P = 0.038) with a similar GLP‐1 staining cell density when compared to the proximal gut. GIP/GLP‐1 co‐staining cells was similar in all studied groups. In T2D patients, the incretin staining cells density in the distal intestine is significantly different from the proximal gut. Thus, a longer RYGB biliopancreatic limb produces a distinctive incretin cell pattern at the gastro‐enteric anastomosis that can result in different endocrine profiles. Abstract : In T2D, incretin cell density in distal and proximal small intestine differs. K/L cells distribution along the small intestine is more homogenous. Different RYGB BPL lengths result in distinctive incretin cell redistributions.